Attitude toward the subject of Chemistry in Australia: An ALIUS and POGIL collaboration to promote cross-national comparisons - Xu, X.; Southam, Daniel; Lewis, J. (The Royal Australian Chemical Institute, 2012)
Networks of educators and researchers that cross international, cultural, and disciplinary boundaries create challenges for comparative measures, even as the network structure invites comparison and collaboration to achieve maximal efficacy. Recognizing that local and contextual issues may impact the interpretation of results, it is important to examine even familiar data when it is gathered in new venues, to ensure that underlying assumptions about the nature of the data remain satisfied. In this example of one such network, Active Learning in University Science, and one such instrument, Attitude toward the Subject of Chemistry Inventory, we explore how using internationally accepted psychometric standards of reliability and validity is important to demonstrate its utility in context beforecross-cultural comparison.